Comparison of bacillary index on slit skin smear with bacillary index of granuloma in leprosy and its relevance to present therapeutic regimens - Sendhil M Kumaran; Ishwara P Bhat; J Madhukara; Pritilata Rout; J Elizabeth (Wolters Kluwer Medknow Publications, 2015)
Background: As the world moves toward elimination of leprosy, persistence of infective cases in endemic pockets remains a significant problem. The use of clinical criteria to decide the paucibacillary (PB) versus multibacillary (MB) regimens has greatly simplified therapy at the field setting. However, a small but significant risk of under-treatment of so-called "PB" cases which actually have significant bacillary load exists. This study was undertaken to assess this risk and compare two methods of assessment of bacillary load, namely bacillary index on slit skin smear (BIS) versus bacillary index of granuloma (BIG). Aims: To compare BIS with BIG on skin biopsy in consecutive untreated cases of leprosy. Materials and Methods: This prospective study was conducted over a period of 12 months, wherein new untreated patients with leprosy were consecutively recruited. After a thorough clinical examination, each patient underwent slit skin smear (SSS) where the BIS was calculated. The same patient also underwent a skin biopsy from a clinical lesion where, the BIG was calculated. SSS and skin biopsy for BIS and BIG respectively were repeated for all patients at the end of therapy for comparison. All patients received therapy according to World Health Organization-Multidrug Therapy Guidelines. Results: The BIG was positive in all cases where the BIS was positive. Significantly, BIG was positive in three cases of borderline tuberculoid leprosy with <5 lesions who received PB regimen, whereas the BIS was negative in all three cases. Conclusion: This study suggests that BIG may be a better indicator of the true bacillary load in leprosy as compared to BIS. Its role in management is significant, at least in tertiary care centers to prevent "under-treatment" of so called PB cases, which may actually warrant MB regimens.